Development of an Industrial Partial Discharge Calibrator and Its Performance Tests - Karaman, Ismail; Ajder, Ali; Nakir, Ismail (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
In industrial electromechanical manufacturing, ensuring the accuracy of electrical partial discharge measurements is crucial for the reliability and efficiency of electrical power systems. The cornerstone of such precision is a well-designed partial discharge calibrator that strictly aligns with the IEC 60270 standard parameters, including apparent charge, rise time, and pulse repetition frequency. This research delineates the systematic development and subsequent performance evaluations of an innovative industrial partial discharge calibrator. The calibrator uniquely integrates advanced functionality while maintaining cost efficiency, offering an alternative to the current partial discharge calibrator market. Its design allows for a broad spectrum of pulse frequency adjustments, making it adaptable to various apparent charge bandwidths and highlighting its adaptability for high-voltage applications. Building upon the foundational understanding of partial discharge as characterized by standards such as IEC 60270, the study underscores the calibrator's capacity to elevate the standards of partial discharge measurements within high-voltage equipment.
Keywords: High voltage; high voltage test techniques; partial discharge; partial discharge calibrator; partial discharge measurements; Computer Science; Engineering; Telecommunications